The effect of the internet on voting behavior - Stephan Heblich (IZA World of Labor, 2016)
The internet has transformed the way in which voters access and receive political information, such that it has circumvented the filtering of information previously undertaken by editorial offices. Consequently, consumers have had to learn how to filter relevant information themselves. The introduction phase of the internet coincided with a decreasing voter turnout, possibly due to “information overload” or less-focused political information. However, the subsequent rise of social media may help reverse the negative effect on turnout. But this poses challenges for regulatory policy. Understanding the internet's effects on the consumption of information is also relevant for how voters view labor policies.
Keywords: D72; L82; L86; 330; internet; voting behavior; mass media; information; social media